2018
DOI: 10.15761/tdm.1000103
|View full text |Cite
|
Sign up to set email alerts
|

FOXF2 differentially regulates expression of metabolic genes in non-cancerous and cancerous breast epithelial cells

Abstract: Forkhead box F2 (FOXF2) functions as a transcription factor and is critically involved in programming organogenesis and regulating epithelial-to-mesenchymal transition (EMT) and cell proliferation. We recently have revealed that FOXF2 can exert distinct functional effects on different molecular subtypes of breast cancer. We found that FOXF2 expression is epigenetically silenced in luminal breast cancers due to its tumor-suppressive role in DNA replication regulation. In contrast, FOXF2 is overexpressed in basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…found that FOXF2 can directly target FOXC2 and transcriptionally inhibit FOXC2 in BLBC cells. FOXC2mediated EMT may be another mechanism by which cancer cells initiate and maintain drug resistance 54 . Therefore, FOXF2 can achieve anticancer effects by inhibiting FOXC2, which suppresses the invasiveness and drug resistance of BLBC cells.…”
Section: Different Roles Of Foxf2 In Different Tumours Breast Cancermentioning
confidence: 99%
“…found that FOXF2 can directly target FOXC2 and transcriptionally inhibit FOXC2 in BLBC cells. FOXC2mediated EMT may be another mechanism by which cancer cells initiate and maintain drug resistance 54 . Therefore, FOXF2 can achieve anticancer effects by inhibiting FOXC2, which suppresses the invasiveness and drug resistance of BLBC cells.…”
Section: Different Roles Of Foxf2 In Different Tumours Breast Cancermentioning
confidence: 99%
“…The present meta-analysis systematically aggregated the data from 16 studies including 8461 cancer patients that assessed the relationship between FOXF2 levels and OS, DFS, RFS, CSS and DMFS. 14,[16][17][18][26][27][28][29][30][31][32][33][34][35][36][37] These current results demonstrated that FOXF2 might be a potentially promising prognostic biomarker. The upregulation of FOXF2 levels was independently associated with better OS (HR ¼ 0.66; 95% CI 0.51, 0.86; P ¼ 0.002) and DFS (HR ¼ 0.60; 95% CI 0.48, 0.76; P < 0.0001).…”
Section: Discussionmentioning
confidence: 71%
“…One dataset each evaluated the association between FOXF2 levels and RFS and DMFS for BC and one dataset examined the association between FOXF2 levels and CSS in ESCC. 18,28,35 The results from two studies indicated that elevated FOXF2 levels were associated with shorter RFS and DMFS among BC patients (HR ¼ 1.25; 95% CI 1.11, 1.39; HR ¼ 2.23; 95% CI 1.16, 3.12; respectively). However, in patients with ESCC, decreased FOXF2 levels were significantly correlated with an unfavourable CSS (HR ¼ 1.71; 95% CI 1.08, 2.71).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations